Quantifying LULC Changes in Constantine, Algeria Using Google Earth Engine: Mapping Land Use/Land Cover Changes in Constantine Through Remote Sensing - Benoumeldjadj, Maya; Rached-Kanouni, Malika; Bouchareb, Abdelouahab; Ababsa, Labed (Future Science, 2024)
The objective of this research is to analyze land use changes in the municipality of Constantine over a thirty year period (1993 – 2023) using Landsat satellite data provided through the Google Earth Engine (GEE) platform and a supervised classification approach. Five land cover classes were mapped at six key dates: water bodies, green spaces, built-up areas, bare soil and agricultural land. The quantified changes highlight a considerable reduction in bare soil in favor of an increase in cultivated land, as well as an expansion of artificial surfaces during certain periods (2008 to 2023). These dynamics reflect the processes of urban sprawl and peri-urbanization at work in this territory. The results obtained demonstrate the potential of remote sensing through GEE for detailed spatio-temporal monitoring of land use. Coupled with other data, this approach contributes to a better understanding of territorial evolutions and provides valuable information for sustainable land use planning.